Use of a Combination of Regional and General Anesthesia during Emergency Thoracic Surgery - V. Kh. Sharipova (Общая реаниматология)
Objective: to elaborate multimodal anesthetic regimens and to evaluate their efficiency during emergency thoracic surgeries for varying injuries. Subjects and methods. A total of 116 patients emergently admitted to the Republican Research Center for Emergency Medical Care for chest traumatic injuries were examined and divided into 3 groups according to the mode of anesthesia. Results. Perioperative multimodal anesthetic regimens for emergency thoracic surgery, which involved all components of the pathogenesis of pain, were elaborated. Conclusion. The combination of regional and general anesthesia contributes to the smooth course of an intra operative period with minimal hemodynamic stress and it is cost effective in decreasing the use of narcotic anal gesics in the intraoperative period.